2021
DOI: 10.3389/fped.2021.622254
|View full text |Cite
|
Sign up to set email alerts
|

Student-Designed Cross-Sectional Pandemic Knowledge Survey of 8th−12th Grade Students, Milwaukee, WI, April 2020

Abstract: Background: The novel coronavirus and its effect on our society are unprecedented. Given the recent pandemic, numerous measures have been taken to protect our communities. We sought to understand our school community's knowledge and the measures that were taken by our school for our safety.Objective: Our objective was to describe the overall understanding and attitudes of 8–12th grade students from a single institution during the initial phase of the Wisconsin's Governor's stay-at-home order.Methods: A volunta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 0 publications
4
3
0
Order By: Relevance
“…Consistent with previous studies, our participants reported obtaining COVID-19 information from various sources, including social media and family. 23 25 , 32 34 Interestingly, the least frequently reported source of COVID-19 information in this study were teachers, which was similar to other studies. 23 , 24 Researchers have expressed concern about the impact of the pandemic on stress, anxiety, depression, and loneliness among students.…”
Section: Discussionsupporting
confidence: 89%
See 4 more Smart Citations
“…Consistent with previous studies, our participants reported obtaining COVID-19 information from various sources, including social media and family. 23 25 , 32 34 Interestingly, the least frequently reported source of COVID-19 information in this study were teachers, which was similar to other studies. 23 , 24 Researchers have expressed concern about the impact of the pandemic on stress, anxiety, depression, and loneliness among students.…”
Section: Discussionsupporting
confidence: 89%
“… 23 25 , 32 34 Interestingly, the least frequently reported source of COVID-19 information in this study were teachers, which was similar to other studies. 23 , 24 Researchers have expressed concern about the impact of the pandemic on stress, anxiety, depression, and loneliness among students. 35 The uncertainty and misunderstanding of our participants regarding social distancing rules is important as young individuals may be avoiding safe activities with a positive impact on their mood and well-being, such as touching pets or walking outside alone.…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations